2020
DOI: 10.1183/13993003.02161-2020
|View full text |Cite
|
Sign up to set email alerts
|

Ivacaftor modifies cystic fibrosis neutrophil phenotype in subjects with R117H residual function CFTR mutations

Abstract: CFTR modulation leads to changes in neutrophil phenotype even in patients with residual function CFTR mutations https://bit.ly/2EUk7xH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Activated neutrophils regulate CFTR distribution by mobilising it to the subcellular sites of activation, while neutrophils with the most common CFTR mutation, F508del, do not achieve this targeting and thus compromise host defence function [ 45 ]. In patients with CF with residual CFTR function, CFTR modulator therapy has been shown to bring about phenotypic changes in neutrophils, consistent with neutrophils becoming less activated [ 46 ]. Polymorphonuclear neutrophil (PMN)-dominated airway inflammation is a feature of CF.…”
Section: The Role Of Cftr In In Nonepithelial Cellsmentioning
confidence: 99%
“…Activated neutrophils regulate CFTR distribution by mobilising it to the subcellular sites of activation, while neutrophils with the most common CFTR mutation, F508del, do not achieve this targeting and thus compromise host defence function [ 45 ]. In patients with CF with residual CFTR function, CFTR modulator therapy has been shown to bring about phenotypic changes in neutrophils, consistent with neutrophils becoming less activated [ 46 ]. Polymorphonuclear neutrophil (PMN)-dominated airway inflammation is a feature of CF.…”
Section: The Role Of Cftr In In Nonepithelial Cellsmentioning
confidence: 99%
“…In addition, studies have observed an increased abundance of neutrophils possessing a pro-survival phenotype within the CF lung [ 73 ]. These neutrophils exhibit reduced apoptosis contributing to the self-perpetuating cycle of inflammation and infection [ 74 , 75 , 76 ].…”
Section: Microbiome In Cfmentioning
confidence: 99%
“…Several trials have proven its efficacy in patients with mild and more advanced disease [142]. More recently, CFTR modulator therapy has been added to the therapeutic repertoire and emerging evidence indicates that these drugs can modulate neutrophil function including beneficial changes in markers of activation [143] and increased bacterial killing [144].…”
Section: Cystic Fibrosismentioning
confidence: 99%